INDUSTRIES AWARENESS ON KOTRA AND THEIR PERCEPTION ON KOTRA SERVICE QUALITY - Harry Istianto; Dimas Haryo Pribadi; Firdaus Alamsjah3 (Journal of Business Strategy and Execution, 2009)
Since 2008, KOTRA Indonesia has focused its strategy on the customer satisfaction enhancement, both in the origin country and destination country. However, there hasn’t been any adequate research to achieve a better understanding of how Indonesia market perceived KOTRA. Further more, there is a concern that Indonesian companies might not very familiar to such international promotion agency like KOTRA regardless the longstanding existence in Indonesia. The main objectives of this thesis are to measure the industries awareness on KOTRA, and how they perceive KOTRA service quality. Methods are using questionnaire and measurement using statistical through mean scores. Complimentary data on import-export volume is also deployed. Results show that industries which are not KOTRA’s customers are not familiar with International Promotional Agencies. Further more, all of Non-KOTRA Customers respondents do not know about KOTRA. However, KOTRA Customers have good understanding in IPA with a very good perception on KOTRA’s service quality. Recommendations given are strongly on the brand awareness building through promoting image and association with Korean products